2022
DOI: 10.1039/d2ta03477h
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio high-throughput screening of transition metal double chalcogenide monolayers as highly efficient bifunctional catalysts for photochemical and photoelectrochemical water splitting

Abstract: Developing efficient bifunctional photocatalysts that can directly split water into hydrogen and oxygen under visible light irradiation has attracted tremendous attention because photocatalytic water splitting is a promising clean technology...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…Recent studies on two-dimensional structures, clusters and visible-light-driven photocatalytic hydrogen evolution reactions are also effective methods for developing hydrogen energy. 22–27 Vos et al . 28,29 reported a high level of single-reference and multi-reference ab initio calculations showing that Be 4 clusters exhibit very efficient Lewis acids when interacting with conventional Lewis bases such as ammonia, water, or hydrogen fluoride.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on two-dimensional structures, clusters and visible-light-driven photocatalytic hydrogen evolution reactions are also effective methods for developing hydrogen energy. 22–27 Vos et al . 28,29 reported a high level of single-reference and multi-reference ab initio calculations showing that Be 4 clusters exhibit very efficient Lewis acids when interacting with conventional Lewis bases such as ammonia, water, or hydrogen fluoride.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recently, several researchers have demonstrated that photocatalytic hydrogen production is one of the proven and effective methods. 3–7 Among masses of efficient semiconductor photocatalysts, graphite carbon nitride (g-C 3 N 4 ) holds unique advantages, such as extremely stable physical and chemical properties, various preparation methods, low cost, and nontoxicity, which is the basis for realizing the industrial application of photocatalytic technology. 8,9 However, g-C 3 N 4 still exhibits only unsatisfactory photocatalytic activity due to its insufficient visible light absorption and fast photogenerated carrier recombination.…”
Section: Introductionmentioning
confidence: 99%
“…7 Replacing oxygen with the less electronegative sulfur and selenide has been the chief hope of rectifying the wide band gap in oxides. So, the past decade has witnessed a surge of interest in the computational screening 12,13 and experimental synthesis of metal chalcogenides as visible-light-driven photocatalysts. 7,14,15 We choose the recently synthesized K 2 Na 2 Sn 3 S 8 and Rb 3 NaSn 3 Se 8 16 as potential candidates for water splitting.…”
Section: ■ Introductionmentioning
confidence: 99%